»Hope dies - Action begins« Stimmen einer neuen Bewegung - Extinction Rebellion Hannover (X-Texte zu Kultur und Gesellschaft, 2019)
"Hope dies - action begins" - this is the motto of the new global environmental movement "Extinction Rebellion" (XR). XR wants to make us all aware of finally taking radical measures against the gigantic species extinction and climate catastrophe. This book features XR activists who explain XR claims, XR principles & values ​​and XR actions from their own point of view. This is intended to encourage readers to engage with this movement and its goals. XR means rebellion for life.